POTENSI LIMBAH PERTANIAN TANAMAN PANGAN SEBAGAI PAKAN TERNAK RUMINANSIA DI KECAMATAN SERAM UTARA TIMUR SETI - Marna Eoh; Ferens Kayadoe (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2021)
This research aims was to determined the types of crop by-product in Seram Utara Timur District and to determined the production of dry matter, crude protein and total digestible nutrients in North East Seti Seram District. Observation and direct measurement of food crop agricultural waste in the three sample villages selected using the purposive sampling method based on the largest number of livestock. The results showed that the types of food crop agricultural waste found in Seram Utara Timur seti sub-district were as follows: rice straw (Oryza sativa L) 96.88%, cassava straw (Manihot esculenta crantz) 1.55% and rice straw (Zea mys), 0.82%. The total agricultural waste of food crops based on dry matter was 11,036.42 tons/ha, crude protein 802.22 tons/ha and total digestible nutrients 6,741.07 tons/ha, and the highest production was in rice straw. The potential of food crop agricultural waste in North Seram District, Timut Seti is quite abundant, it is hoped that beef cattle breeders can utilize food crop agricultural waste as ruminant animal feed.